Molecular detection of feline leukemia virus in clinically ill cats in Klang Valley, Malaysia - Mummoorthy, Kunambiga; Abd Rahaman, Yasmin; Arshad, Siti Suri; Omar, Abdul Rahman; Saulol Hamid, Nur Fazila; Anand, Prem; Liew, Wuan Hoong; Kiven Kumar (Veterinary World, 2021)
Background and Aim: Feline leukemia virus (FeLV) is classified as Retroviridae gammaretrovirus. FeLV occurs worldwide, including Malaysia. Thus far, only one decade-old study on molecular characterization of Malaysian FeLV isolates exists, which resulted in a scarcity of updated information of current FeLV isolates circulating in Malaysia. This study was conducted to determine the status of FeLV in clinically ill cats and to study the molecular characterization and phylogenetic relatedness of the current isolates. Materials and Methods: Convenience sampling was performed in 20 cats from the Gasing Veterinary Hospital in Selangor. Plasma and saliva samples were collected from 15 clinically ill cats and 5 healthy cats subjected to one-step reverse transcription-polymerase chain reaction with primers targeting a highly conserved gene of U3-LTR-gag. Results: Two clinically ill cats' plasma and saliva samples tested positive for FeLV RNA. Partial nucleotide sequencing and phylogenetic analysis revealed that the current isolates were 94-99% homologous to the previous Malaysian and Japanese FeLV isolates. Conclusion: Current FeLV isolates from this study displayed higher similarity with the previous Malaysian isolates, signifying that a similar FeLV strain circulated among the cat population in Selangor.